The Description Of Birth Preparedness For Pregnant Women In The Third Trimester Based The KIA Book at Mentok Public Health Center 2025 - Yandria, Rizki; Astuti, Ratnaningsih Dewi; Shinta Yuka, Aprillia Ayu; Taswin, Muhammad; Komariah, Nurul (Poltekkes Kemenkes Palembang, 2025)
Pregnancy and childbirth are a natural process; however, in the process, pregnant women and their families need to understand, one of which is about birth preparedness. The unpreparedness of pregnant women in facing childbirth is one of the factors causing the maternal mortality rate. The high maternal mortality rate indicates that maternal health is still low. Supporting efforts to improve the quality of maternal health service to reduce maternal mortality rate, the government is empowering families with a program for ownership and utilization of KIA books. The KIA book details for birth preparedness including estimated birth date, birth companion, place and assistant of delivery, savings and emergency cost for childbirth, vehicle preparation, blood donation, mother and baby equipment, important document, and plans to contraception method (KB). The result of the preliminary study showed that birth preparedness for pregnant women in the third trimester based on the KIA book is still low. The main aim of the study was to compare the description of birth preparedness for pregnant women in the third trimester based on the KIA book at Puskesmas Mentok, 2025. The type is research a quantitative descriptive observational design with a cross sectional study. The population consist of all pregnant women in the third trimester to visiting Puskesmas Mentok in March 2025 period, amounting to 50 respondents. Sampling was caried out using the total sampling technique. There are still around (8%) of pregnant women in the third trimester who are birth preparedness in a less than good approach. The risk of complicatons during pregnancy and childbirth is still high, one of which is when a pregnant woman experiences bleeding and requires special assistance in the form of a blood transfusion, but the pregnant woman does not yet have a candidate blood donation to prepare of emergencies.